Impact of sheath size and hemostasis time on radial artery patency after transradial coronary angiography and intervention in Japanese and non-Japanese patients: A substudy from RAP and BEAT (Radial Artery Patency and Bleeding, Efficacy, Adverse evenT) randomized multicenter trial - Aminian, Adel; Saito, Shigeru; Takahashi, Akihiko; Bernat, Ivo; Jobe, Robert Lee; Kajiya, Takashi; Gilchrist, Ian C; Louvard, Yves; Kiemeneij, Ferdinand; van Royen, Niels; van Leeuwen, Maarten; Yamazaki, Seiji; et al. (Catheterization and cardiovascular interventions, 2018)
BACKGROUND: During transradial (TR) access, it remains unclear whether differences in baseline patients characteristics and hemostasis care impact the rate of radial artery occlusion (RAO). We sought to compare the rate of RAO after TR access with the 6 French(Fr) Glidesheath Slender (GSS6Fr, Terumo, Japan) or a standard 5 Fr sheath in Japanese and non-Japanese patients. METHODS AND RESULTS: The Radial Artery Patency and Bleeding, Efficacy, Adverse evenT (RAP and BEAT) trial randomized 1,836 patients undergoing TR coronary angiography and/or interventions to receive the GSS6Fr or the standard 5 Fr Glidesheath (GS5Fr, Terumo, Japan). Out of this study population, 1,087 were Japanese patients and 751 non-Japanese patients. The overall incidence of RAO was significantly higher in Japanese patients (3.6% vs. 1.2%, P = 0.002). Use of GSS6Fr was associated with higher rates of RAO than GS5Fr in Japanese patients (5% vs. 2.2%, P = 0.02) and with similar RAO rates in non-Japanese patients (1.3 vs. 1.1%, P = 1). The mean hemostasis time was significantly longer in Japanese patients (378 ± 253 vs. 159 ± 136 min, P < 0.001) and more Japanese patients had a hemostasis time of more than 6 hr (16.2% vs. 4.9%, P < 0.0001). Longer hemostasis time was an independent predictor of RAO (OR per additional hour 1.070, 95% CI 1.008-1.136, P = 0.03). CONCLUSIONS: Use of GSS6Fr was associated with a higher rate of RAO than a standard 5 Fr sheath in Japanese patients but not in non-Japanese patients. Whether improvement in post-procedural care and reduced hemostasis time could impact the incidence of RAO in Japanese patients should be further assessed.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; Radial Artery; hemostáza; Hemorrhage; Spojené státy americké; Humans; průchodnost cév; srdeční katétry; lidé středního věku; koronární angioplastika; Japonsko; Equipment Design; Female; rizikové faktory; Aged; výsledek terapie; Catheterization, Peripheral; Arterial Occlusive Diseases; senioři; arteriální okluzní nemoci; lidé; Japan; United States; časové faktory; arteria radialis; periferní katetrizace; koronární angiografie; ženské pohlaví; Single-Blind Method; Male; Hemostasis; Middle Aged; incidence; Incidence; design vybavení; Treatment Outcome; Aged, 80 and over; Coronary Angiography; Percutaneous Coronary Intervention; senioři nad 80 let; krvácení; Cardiac Catheters; jednoduchá slepá metoda; mužské pohlaví; prospektivní studie; Asian People; Time Factors; Asijci; Vascular Patency; Risk Factors; Prospective Studies